The European Union’s security relations with asian partners - Christiansen, Thomas; Kirchner, Emil J.; Tan, See Seng (Palgrave Macmillan, 2021)
This wide-ranging book analyses EU-Asia security relations in a systematic, substantive and comparative manner. The contributions assess similarities and differences between the EU and its Asian partners with respect to levels of threat perception, policy response and security cooperation in the context of historical, institutional and external factors – such as the influence of the United States. The book presents original empirical research organised in four parts: a number of contributions providing discussions of the global context in which EU-Asia security relations develop; a series of chapters covering the range of dimensions of EU-Asian security, including both traditional and non-military aspects of security; chapters addressing the specific issues touching on bilateral relations between the EU and its partners in the Asia-Pacific region; and a final part presenting the overall findings across the various contributions together with the future outlook for EU-Asia security relations. Thomas Christiansen is Professor of Political Science and European Integration at Luiss University, Rome, Italy. He is Executive Editor of the Journal of European Integration. Emil Kirchner is Jean Monnet Chair and Emeritus Professor at the University of Essex, UK. See Seng Tan is President and CEO of International Students Inc. (ISI), a faith-based organisation in the US, and concurrently Professor of International Relations at Nanyang Technological University in Singapore.
Keywords: Europäische Union; Asien